Studying the Structure of Al–Mg–Si Casting Alloys Doped by Lithium - Trudonoshyn, Oleksandr (Physics of Metals and Metallography, 2020)
Abstract: The article discusses changes in the structure of Al–Mg–Si cast alloys after their additional alloying with lithium. To predict and explain the phase transformations in the studied alloys, phase diagrams were calculated using Thermo-Calc software. Thermo-Calc results are in good agreement with microstructure analysis. The morphology and chemical composition of the intermetallic phases were studied using a scanning electron microscope and EDX analysis on polished and deeply etched microsections. There were revealed several intermetallic phases in the studied alloys. It was found that the addition of lithium has a modifying effect on the structure of the studied alloys, which also leads to the formation of a new AlLiSi phase. To analyze the effect of lithium on the mechanical properties, the Brinell hardness, tensile strength, yield strength, and elongation were measured. Additional alloying with lithium leads to an increase in the strength properties of the studied alloys compared to the base alloy.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Al–Mg–Si alloys; lithium; microstructure; phase diagrams